Histopathology of endometrium in abnormal uterine bleeding, in correlation with thyroid profile and ultrasonography findings - Gorla, Parvathi; Sanapala, Sridevi; Devi, Eswari; Atla, Bhagya Lakshmi; Rasaputra, Manasa (International Journal of Research in Medical Sciences, 2016)
Background: Abnormal uterine bleeding is the cause for many disturbances in women who are in the reproductive age group. Frequent and prolonged periods will lead to morbidity, social embarrassment, diminished quality of life and compromise of the sexual life. Methods: It is a hospital based cross sectional study conducted in the department of pathology, Andhra medical college. A total of 270 patients in the age group of 18 to 45 years were included in this study. Endometrial samples were obtained and histopathological examinations were conducted. All the clinical details and investigation reports were collected. Results: The age group of patients in this study ranged from 18 to 45 years. Maximum numbers of cases (169) were in the age group of 36 to 45 years (62.6%). Most of the patients were multipara (244 cases, 90.37%) and most common presenting complaint was heavy menstrual bleeding (198 cases, 73.3%). Majority of the patients were euthyroid (247 cases, 91.5%). Normal cyclical endometrium was found to be the commonest histopathological pattern with proliferative endometrium in 45.56% and secretory endometrium in 32.59% cases. Leiomyomas were found to be the commonest cause of abnormal uterine bleeding (15.56%). Bulky / enlarged uterus (77%) and type-IV (hyperechoic) endometrium, depicting the secretory endometrial pattern (36.66%) was the most common finding on transvaginal sonography (TVS). Conclusions: Histopathological examination is the gold standard for studying the pattern of endometrium in various causes of abnormal uterine bleeding.